VARS-TOOL: A toolbox for comprehensive, efficient, and robust sensitivity and uncertainty analysis. (February 2019) - Razavi, Saman; Sheikholeslami, Razi; Gupta, Hoshin V.; Haghnegahdar, Amin
Abstract: VARS-TOOL is a software toolbox for sensitivity and uncertainty analysis. Developed primarily around the " Variogram Analysis of Response Surfaces " framework, VARS-TOOL adopts a multi-method approach that enables simultaneous generation of a range of sensitivity indices, including ones based on derivative, variance, and variogram concepts, from a single sample. Other special features of VARS-TOOL include (1) novel tools for time-varying and time-aggregate sensitivity analysis of dynamical systems models, (2) highly efficient sampling techniques, such as Progressive Latin Hypercube Sampling (PLHS), that maximize robustness and rapid convergence to stable sensitivity estimates, (3) factor grouping for dealing with high-dimensional problems, (4) visualization for monitoring stability and convergence, (5) model emulation for handling model crashes, and (6) an interface that allows working with any model in any programming language and operating system. As a test bed for training and research, VARS-TOOL provides a set of mathematical test functions and the (dynamical) HBV-SASK hydrologic model. Highlights: Introduces a next-generation toolbox for sensitivity and uncertainty analysis. Provides a multi-method approach that unifies different theories and strategies. Accounts for dynamical properties of Earth and environmental systems models. Provides various sampling strategies including progressive Latin hypercube sampling. Facilitates handling of high-dimensional models with hundreds of uncertain factors.